SISTEM PENGELOLAAN LIMBAH B3 TERHADAP INDEKS PROPER DI RSPI PROF. DR. SULIANTI SAROSO - Anggraini, Fauziah; Rahardjo, Mursid; Setiani, Onny (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
RSPI Prof. Dr. Sulianti Saroso is a hospital that has received ratings blue for PROPER. The hospital is classified in the government hospitals with the classification of type B education. The average amount of harzardous and toxic waste generated as much as 80.55 kg / day with an average number of patient visits as many as 391 people / day. Based on the field observations that has done, the management of hazardous and toxic waste in this hospital has not managed well arcconding to Government Regulation No. 101 in 2014, Environment Minister Decision No.r 06 in 2013 and Health Minister Decision No. 1204 in 2004. The purpose of this study was to assess the management of hazardous and toxic waste to PROPER index in RSPI Prof. Dr. Sulianti Saroso. This research methodology used in this research was qualitative and quantitative approaches with cross sectional design. The population of this study was executing management of hazardous and toxic wastes by using total sampling technique. The results showed data types and volume hazardous and toxic waste management, reporting activity of hazardous and toxic waste management, license and validity period hazardous and toxic waste management, the implementation of permit conditions, the amount of waste managed hazardous and toxic, and hazardous and toxic waste management with third-party, Based on Health Minister Decision No. 1204 in 2004 lug process, transportation, storage and management of B3 waste management not eligible. Based on the results of this research hazardous and toxic waste come from 7 hospital primary care with various types of hazardous and toxic was syringes, plabot, scalpel, infusion hoses, catheters hoses, tissue and fluids body, the result of assessment hazardous and toxic waste management by 70% and PROPER ranking was blue.